Exercise in Pregnancy: The Impact of an Intervention Program in the Duration of Labor and Mode of Delivery - Cátia Liliana Martins Ferreira; Cláudia Maria Lopes Guerra; Ana Isabel Teixeira Jesus Silva; Helena Rafaela Vieira do Rosário; Maria Beatriz Ferreira Leite de Oliveira Pereira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To access the benefits or harms of an exercise program, based on the current American College of Obstetricians and Gynecologists guidelines, on the mode of delivery, duration and onset of labor. Methods A study performed at the Hospital Senhora da Oliveira between October 2015 and February 2017. This was a quasi-experimental study involving 255 women divided into two groups: an intervention group engaged in a controlled and supervised exercise program during pregnancy (n = 99), and a control group that did not participate in the exercise program (n = 156). Data were collected in two stages: during the 1st trimester biochemical screening (before the beginning of the program), through a written questionnaire, and after delivery, from the medical files of the patients. The significance level in the present study was 5% (p = 0.05). Results The control group had higher odds of induced labor (odds ratio [OR] 2.71; 95% confidence interval [CI]: 1.42-5.17; p = 0.003), when compared with women who underwent the intervention. No differences were found between the groups in instrumental vaginal deliveries, cesarean rate, time until the beginning of the active phase, duration of the active phase, and duration of the second stage of labor. Conclusion The implementation of a controlled and supervised exercise program in pregnancy was associated with significantly lower odds of induced deliveries.